Retronasal Olfaction Test Methods: A Systematic Review - Hüseyin Özay; Aslı Çakır; Mustafa Cenk Ecevit (Balkan Medical Journal, 2019)
Background: This report produces a bibliographic study of psychophysical tests proposed clinical assessments of retronasal olfaction. Aims: We review how these tests can be utilized and discuss their methodological properties. Study Design: Systematic review. Methods: We undertook a systematic literature review investigating the retronasal olfaction test methods. PubMed, the free online MEDLINE database on biomedical sciences, was searched for the period from 1984 to 2015 using the following relevant key phrases: “retronasal olfaction”, “orthonasal olfaction”, “olfaction disorders”, and “olfaction test”. For each of the selected titles cited in this study, the full manuscript was read and analyzed by each of the three authors of this paper independently before collaborative discussion for summation and analytical reporting. Two reviewers independently read the abstracts and full texts and categorised them into one of three subgroups as follow, suitable, not-suitable, and unsure. Then they cross-checked the results, and a third reviewer decided assigned the group “unsure” to either the suitable group or the not-suitable group. Fifty eight studies revealed as suitable for review by two authors whereas 13 found not suitable for review. The total amount of 60 uncertain (unsure) or differently categorized articles were further examined by the third author which resulted in 41 approvals and 19 rejections. Hence 99 approved articles passed the next step. Exclusion criteria were reviews, case reports, animal studies, and the articles of which methodology was a lack of olfaction tests. By this way excluded 69 papers, and finally, 30 original human research articles were taken as the data. Results: The study found that the three most widely used and accepted retronasal olfaction test methods are the retronasal olfaction test, the candy smell test and odorant presentation containers. All of the three psychophysical retronasal olfaction tests were combined with orthonasal tests in clinical use to examine and understand the smell function of the patient completely. There were two limitations concerning testing: “the lack concentrations and doses of test materials” and “performing measurements within the supra-threshold zone”. Conclusion: The appropriate test agents and optimal concentrations for the retronasal olfaction tests remain unclear and emerge as limitations of the retronasal olfaction test technique. The first step to overcoming these limitations will probably require identification of retronasal olfaction thresholds. Once these are determined, the concept of retronasal olfaction and its testing methods may be thoroughly reviewed.